Development of the Croatian model of organ donation and transplantation - Živčić-Ćosić, Stela (Croatian Medical Schools, 2013)
During the past ten years, the efforts to improve and organize the national transplantation system in Croatia have resulted in a steadily growing donor rate, which reached its highest level in 2011, with 33.6 utilized donors per million population (p.m.p.). Nowadays, Croatia is one of the leading countries in the world according to deceased donation and transplantation rates. Between 2008 and 2011, the waiting list for kidney transplantation decreased by 37.2% (from 430 to 270 persons waiting for a transplant) and the median waiting time decreased from 46 to 24 months. The Croatian model has been internationally recognized as successful and there are plans for its implementation in other countries. We analyzed the key factors that contributed to the development of this successful model for organ donation and transplantation. These are primarily the appointment of hospital and national transplant coordinators, implementation of a new financial model with donor hospital reimbursement, public awareness campaign, international cooperation, adoption of new legislation, and implementation of a donor quality assurance program. The selection of key factors is based on the authors' opinions; we are open for further discussion and propose systematic research into the issue.